2019
DOI: 10.1136/neurintsurg-2019-015311
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of non-trunk basilar perforator aneurysms: is it worth chasing the small fish?

Abstract: Background and purposeNon-trunk basilar artery perforator aneurysms (BAPAs) are rare intracranial vascular pathologies that have long been underdiagnosed, under-reported, and under-analyzed. We performed a systematic review of the efficacy and safety endpoints between conservative and active treatment approaches for non-trunk BAPAs.MethodsMajor databases were analyzed for relevant publications between 1995 and 2019. Studies comparing the outcomes between conservative and active treatment approaches such as coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…The re-evaluation showed that all negative results in the initial DSA examinations were true negatives. Nonetheless, in our series, only 28% of the aneurysms were diagnosed on the initial angiographic imaging study, which is in line with recent systematic reviews of non-trunk BAPAs by Granja et al [1] and of posterior circulation perforator aneurysms by Gardijan et al [14] reporting diagnosis of the aneurysm on the first DSA study in 50% and 39%, respectively. In absence of a confirmed rebleeding, we tried to perform the repeat DSA after confirmation of resolution of SAH-related vasospasm, using transcranial Doppler.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The re-evaluation showed that all negative results in the initial DSA examinations were true negatives. Nonetheless, in our series, only 28% of the aneurysms were diagnosed on the initial angiographic imaging study, which is in line with recent systematic reviews of non-trunk BAPAs by Granja et al [1] and of posterior circulation perforator aneurysms by Gardijan et al [14] reporting diagnosis of the aneurysm on the first DSA study in 50% and 39%, respectively. In absence of a confirmed rebleeding, we tried to perform the repeat DSA after confirmation of resolution of SAH-related vasospasm, using transcranial Doppler.…”
Section: Discussionsupporting
confidence: 91%
“…Perforating artery aneurysms of the anterior circulation are a rare subtype of intracranial aneurysms (prevalence < 1%) [1,2]. Basilar artery perforator aneurysms (BAPAs) are even less common, with a recent systematic literature review by Granja et al [1] describing only 56 cases of nontrunk type BAPAs since their initial description in 1996 [3]. Categorizing BAPAs is a challenging task due to a potential overlap with so-called blister-like aneurysms of the basilar artery trunk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…and are extremely rare [1] . About 80 cases have been reported in literature thus far, and their diagnosis and management are challenging [2] , [3] , [4] , [5] . Because of their small size, detection on computed tomography angiography (CTA), magnetic resonance angiography (MRA) imaging, and digital subtraction angiography (DSA) is difficult and often repeated DSA is needed to confirm the diagnosis.…”
Section: Introductionmentioning
confidence: 99%